(untitled) (Revista Direito em Debate, 2021)
This article aims, based on the concept of judicialization of politics developed by Gallo (2009), Barroso (2009), Sadek (2004) and Ramos and Diniz (2016), to deal with how this phenomenon appears in Latin America, notably, in Brazil and Chile, and then analyze its possible consequences. It is assumed that judicialization is a globalized phenomenon that involves several issues and that although debt opinions should not necessarily be seen as something negative. To achieve the intended scope, a systematic review of the literature was carried out with extensive bibliographic research in books by national and international authors, stratified scientific articles with qualis periodical evaluated with extract “A” and “B” and/or constant in databases such as Scopus, LILACS and Google Scholar, as well as works found at the Brazilian Digital Library of Theses and Dissertations (BDTD).